Strategi Pengembangan Potensi Wisata Bahari di Pantai Atuh Desa Pejukutan Kecamatan Nusa Penida Kabupaten Klungkung - Wibawa, I Putu Ngurah; Sunarta, I Nyoman (JURNAL DESTINASI PARIWISATA; Vol 7 No 1 (2019): VOL 7, NO 1 (2019): (JANUARY-JUNE) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2019.v07.i01.p19, 2019)
Pejukutan Village has very good natural and maritime potential, one of which is Atuh Beach's tourism potential which has a white sand beach with very good reefs, Melonteng Hill, Tree House, Diamond Clip besides that at Atuh Beach, there are 4 (four) islands large coral, namely Batu Melawang or Pepadasan Island, Batu Paon Island, Batu Abah Island and Batu Jineng Island, this is one of the attractions of Atuh Beach. In this study, the data obtained by way, observation, in-depth interviews, documentation studies, literature study. Using data types in the form of qualitative and quantitative, while the data source in the form of primary data and secondary data. Data analysis used in this research is descriptive qualitative analysis and analysis SWOT matrix (Strength, Weaknesses, Opportunities, Threats). The results research is Atuh Beach as a marine tourism and natural tourism with the potential possessed such as the scenery possessed by Atuh Beach which is flanked by two hills from the left and right, underwater scenery, has coral islands such as Batu Melawang Island or Pepadasan ( Batu Bolong), Batu Paon Island, Batu Abah Island and Batu Jineng Island, Melonteng Hill, Throwing Tree House and Diamond Clip. the people of Pcantutan Village are mostly farmers. Aside from being a farmer in the Potanutan Village community, they are also craftsmen in weaving and raising livestock. The Village of Pejukutan has Baris Jangkang Dance, this dance is performed when accompanying certain ceremonies.   Keyword : Strategy Development, Potency, Maritime Tourism